GROWTH AND YIELD OF Calliandra calothyrsus PLANTS AT VARIOUS DOSES AND FREQUENCIES OF GOAT BIOURINE FERTILIZER APPLICATION - A., Purba; Suarna, I W.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
One step to overcome forage limitations is to utilize Calliandra calothyrsus legume plants . This study aimed to determine the interaction between the dose and frequency of use of goat biourine on the growth and yield of Calliandra calothyrsus plants. Goat biourine fertilizer can be an alternative because it has a high organic matter content, namely nitrogen (N) 36.90 - 37.31%, phosphate (P) 16.5 -16.8 ppm, and potassium (K) 0.67 - 1.27%. The research was conducted in Green House Sesetan Research Station, Faculty of Animal Husbandry Udayana University, and lasted for 10 weeks. The study used a complete randomized design (CRD) factorial pattern with two factors.  The first factor was the dose of fertilizer consisting of D0=0 l ha-1, D1=2500 l ha -1 , D2=5000 l ha -1 , D3=7500 l ha -1 , D4=10000 l ha -1 The second factor was the frequency of fertilizer application F1=1 time F2=2 times F3=3 times. There 15 treatments and each treatment was repeated 3 times so 45 units of research were needed. The variables observed were growth, yield, and growth characteristics variables. The results of the research showed that treatment with a dose of 0 l ha -1 , 2500 l ha -1 , 7500 l ha -1 , and 10000 l ha -1 showed a lower effect than the dose of 5000 l ha -1 on the growth and yield variables of Calliandra calothyrsus plants. A frequency of 3 times goat biourine fertilizer tends to show better growth and yields than a frequency of 1 and 2 times. It can be concluded that giving a dose of 5000 l ha -1 of goat biourine fertilizer and a frequency of 3 times the application tends to show the best growth and results of Calliandra calothyrsus plants. There was an interaction between the dose and frequency of goat biourine fertilizer application on plant height variables and the ratio of dry weight of leaves to stems dry weight of Calliandra calothyrsus .